EXAMEN ESPECIAL A LAS CUENTAS: INVENTARIOS Y CUENTAS POR PAGAR EN SURECTEL INGENIERÍA Y PROYECTOS CÍA. LTDA DE LA CIUDAD DE LOJA, PERIODO 2013 - Sarmiento Venegas, Karen Dianne (2016)
The thesis work entitled "SPECIAL REVIEW ACCOUNTS: INVENTORIES AND ACCOUNTS PAYABLE IN SURECTEL ENGINEERING AND PROJECTS CO. LTDA LOJA CITY, PERIOD 2013 "was aimed at: assessing the internal control system implemented by the entity; check the level of compliance with the rules and procedures of the Inventory and Accounts Payable Items; verify the reasonableness of the amounts presented items Inventories and Accounts Payable, and formulate the period 2013 special examination report containing comments, conclusions and recommendations in order to improve internal control of the entity which may lead to the taking of accurate decisions. To fulfill the objectives we proceeded to make the visit to the institution, they executed interviews the manager and staff working in the state was formulated; Likewise it was collected and analyzed information supporting documents. By developing the financial audit process consisting of three phases: planning, execution and reporting of results. The planning is divided into two phases which are the preliminary planning in which general information about the entity and the main activities related to the examined accounts and specific planning in which the internal control questionnaire was developed was obtained the same that allowed evaluate and rate risks, presenting a high risk level and a low level of confidence of 40% in terms of inventories; and a low level of risk and a high level of confidence of 80% in accounts payable and finally a report containing the findings during the special examination described was developed. The main results obtained are cited: the breach of the rules and procedures of the inventory and accounts payable accounts generated by the lack of a physical space for inventory, lack of physical counts of inventory, lack of a warehouse keeper, protection and restricted to hold and slow-moving inventories access; without treatment or policies to improve their control and not the same standards apply policies for accounts payable processing frame old balances and charging interest for late payments. The balances of the accounts examined except lack of identified controls are reasonable, records of transactions have been made in a timely manner, and reviewed the relevant documentation as journal, ledger, invoices verifying that existing balances the financial statements are fairly presented. Situations that are reflected in the special examination report which contains comments, conclusions and recommendations will serve the authorities of the entity being reviewed to improve operations and achieve greater efficiency, effectiveness and efficiency. The special examination SURECTEL the company ENGINEERING PROJECTS CO. LTDA LOJA CITY, PERIOD 2013, is underpinned by a series of working papers that are the material evidence of the work performed.